Complexity of projective methods for the solution of ill-posed problems - Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We consider the problem of finite-dimensional approximation for solutions of equations of the first kind and propose a modification of the projective scheme for solving ill-posed problems. We show that this modification allows one to obtain, for many classes of equations of the first kind, the best possible order of accuracy for the Tikhonov regularization by using an amount of information which is far less than for the standard projective technique.